Vitamin-mineral complexes as a protector of obstetric and perinatal complications (review of literature) - Tatyana Yu Pestrikova; Elena A Yurasova (IP Berlin A.V., 2019)
Relevance. Despite the achievements of modern medicine, the problem of reducing complications of the gestational period and perinatal outcomes still does not lose its relevance. Lack of security and/or unbalanced consumption of vital micronutrients are factors of constant negative impact on health, growth, development and formation of organs and systemogenesis in all age periods. Unbalanced nutrition, in particular vitamin deficiency conditions, is considered by the World Health Organization as a problem of starvation, which has a direct impact on the incidence and mortality of the population. Aim. Analysis of literary sources to identify the effect of vitamin-mineral complexes on pregnancy and perinatal outcomes. Materials and methods. To write this review, we searched for domestic and foreign publications in Russian and international search engines (PubMed, eLibrary, etc.) over the past 30 years. The review included articles from peer-reviewed literature. Results. The review addresses balanced nutrition for pregnant women who receive close attention throughout the world. The optimal provision of vitamins and minerals for women during the gestational period, when the need for essential micronutrients is significantly increased, is a prerequisite for the physiological course of pregnancy and the full development of the fetus. This is especially important in the conditions of the northern and equivalent territories. The need for vitamins in women during pregnancy and lactation increases by 1.5 times, due to the intensive work of the endocrine system of women, the transfer of some nutrients to the fetus. Deficiency of certain vitamins is a risk factor for the development of birth defects, premature birth, and the birth of children with low body weight. Conclusions. The domestic combined vitamin-mineral preparation with micro and macro elements was created specifically taking into account the changing needs of the woman's body for vitamins and minerals at different stages of pregnancy. Compatibility of components in 1 tablet is provided by special production technology.